PENDEKATAN SISTEM DALAM TINJAUAN FILSAFAT: ONTOLOGI, AKSIOLOGI, DAN EPISTEMOLOGI - Erli Yanty Rihana Paramida; Dini Prima Putri; Romlah; Saiful Anwar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research examines the systems approach in the context of philosophy with a focus on three main aspects: ontology, axiology, and epistemology. Ontology addresses the nature of reality and entities in systems, highlighting how interactions between elements shape the entire system. Axiology explores the values ​​underlying the systems approach, including the ethical and normative considerations that play a role in decision making. Meanwhile, epistemology examines the way knowledge is built and understood within a systemic framework, as well as its implications for research methods and the application of theory. By using a qualitative approach, this research integrates various literature and philosophical thinking to provide a comprehensive understanding of the relevance of the systems approach in contemporary philosophy. It is hoped that the results of this research can contribute to the development of systems theory and its application in various scientific disciplines.